2011
DOI: 10.1128/jvi.00790-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Comparison of Chronic Wasting Disease Infectivity from Deer with Variation at Prion Protein Residue 96

Abstract: Chronic wasting disease (CWD) is a prion disease of cervids that causes neurodegeneration and death. Susceptibility to prion infections, including CWD, can be dependent on the amino acid sequence of the host prion protein (PrP). Here, CWD agent obtained from a deer expressing the 96SS genotype, associated with partial resistance to CWD, was used to infect transgenic (tg) mice expressing either 96GG or 96SS deer PrP. Transgenic mice expressing 96GG deer PrP succumbed to this agent, but tg mice expressing 96SS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 28 publications
4
46
0
Order By: Relevance
“…Previous studies consistently showed Tg60 mice expressing deer PrP-S96 to be entirely resistant to CWD, and investigators were unable to identify PrP Sc in the brains of asymptomatic Tg60 mice (26,27). Our results show that after long incubation times CWD-infected Tg(DeerPrP-S96)7511 +/− mice were ultimately susceptible to disease, albeit with incomplete attack rates.…”
Section: Discussion Prp Polymorphisms Operate By Distinct Mechanisms mentioning
confidence: 46%
“…Previous studies consistently showed Tg60 mice expressing deer PrP-S96 to be entirely resistant to CWD, and investigators were unable to identify PrP Sc in the brains of asymptomatic Tg60 mice (26,27). Our results show that after long incubation times CWD-infected Tg(DeerPrP-S96)7511 +/− mice were ultimately susceptible to disease, albeit with incomplete attack rates.…”
Section: Discussion Prp Polymorphisms Operate By Distinct Mechanisms mentioning
confidence: 46%
“…Of these polymorphisms, Q95, G96, and A116 are more common in the deer population and reported with higher frequency in natural cases of CWD (18). Studies have demonstrated at least one copy of the S96 allelic variation prolongs the CWD incubation period in deer, up to 230%, and appears to impede but not prevent PrP CWD conversion (2,19,20).…”
mentioning
confidence: 99%
“…CWD accumulation and prolonged survival (and perhaps partial resistance to natural infection) associated with the glycine to serine change at position 96 of the white-tailed deer PRNP gene (Johnson et al, 2006(Johnson et al, , 2011Meade-White et al, 2007;Race et al, 2011) is similar to the influences of a serine to phenylalanine change at PRNP position 225 on PrP CWD accumulation and survival in mule deer (Fox et al, 2006). Variation among white-tailed deer sampled here should afford opportunities to evaluate genetic influences on agent shedding once appropriate tools have been developed.…”
Section: Prpmentioning
confidence: 86%
“…Samples collected during this study were shared with at least five other institutions, and some of these collaborations have helped advance scientific understanding of CWD and prion diseases in general (Chang et al, 2007;Wolfe et al, 2007;Tamgü ney et al, 2009Tamgü ney et al, , 2012Race et al, 2011;Rubenstein et al, 2011). Other studies are under way using materials arising from our work, and additional endeavors will be supported as feasible.…”
Section: Prpmentioning
confidence: 99%